Simulasi Populasi Mikroba Menggunakan Teknologi Smart Biosoildam untuk Daya Dukung Tanah Margel - Nugroho Widiasmadi (Departement of Mathematics Education, 2023)
This study aims to determine the ability of the margel soil layer to distribute nutrients and restore soil health and fertility due to the use of chemical fertilizers and pesticides. This method uses Smart Biosoildam (Biodam) technology which can be simulated to match the actual process (real time). From the observation of graphs and EC standards it can be seen that the ability of the soil to lower the level of acids and increase fertility. Janis this soil until day 42 the soil fertility rate has not reached = 900 uS/cm with microbial populations = 10 3/cfu to support the vegetative growth period as well as in the generative growth period, so that we will know when is the right time to do: soil recovery through nutrient infiltration, early planting of bulbs/flowers/fruits can begin to be conditioned. until mature based on nutritional value observed through sensors that convert analog parameters by the microcontroller into digital information transmitted via WiFi in real time. The initial condition before the simulation of soil fertility values with EC parameters was 444 uS/cm, the simulation results were: Simulation 1 : Nutrient content for generative growth was achieved on day 27 with fertility rate = 1025 uS/cm with Microbial Population 10 8/cfu. Simulation 2: Nutrient content for generative growth was achieved on day 42 at fertility rate = 1100 uS/cm with microbial population = 105/cfu. Simulation 3: the content of nutrients for generative growth cannot be observed